Mass Incarceration and Microaggressions: America’s Modern Day Slavery - Tadros, Eman; McCaskill, Arika (Utan Kayu Publishing, 2023)
The Black population has historically been disregarded, abused, and overlooked. Its past and present are still marred by white supremacy which displays itself in various ways. This includes but is not limited to racism in the justice system, law enforcement, sports, home-buying, educational institutions, etc. Some members of the Black population have been successful at navigating this reality while others struggle to persevere. Further, individuals of any race can and do engage in criminal behavior, but it is people of color that are incarcerated at disproportionate rates. Facing the stress of an unjust world on a daily basis can manifest physically emotionally, and mentally. This paper analyzes the effects of mass incarceration and microaggressions on Black Americans.